Pengaruh Phubbing terhadap Interaksi Sosial Siswa Kelas X SMAN 3 Jember - Sofianta, Nurma (FKIP Universitas Islam Jember, 2021)
The purpose of this study was to find out whether or not the influence of phubbing behavior on the social interaction of class X students in SMA N 3 Jember. The research method used is descriptive analysis correlation. The population used as objects in this study are students of class X SMA N 3 Jember in the 2019-2020 school year. The sample in this study were 170 students. The results of the study were calculated with the Pearson Product Moment Test, with a significance level of 5% and N 170 obtained r count of 0.306 and r table of 0.1497. After r count compared to r table it turns out that r count is greater than r table that is 0.306> 0.1497. thus it can be concluded that the hypothesis (ha: phubbing behavior influences the level of communication quality of class X students of SMA N 3 Jember can be accepted).